2009
DOI: 10.1242/dev.028365
|View full text |Cite
|
Sign up to set email alerts
|

The polarly localized D6 PROTEIN KINASE is required for efficient auxin transport inArabidopsis thaliana

Abstract: The phytohormone auxin is a major determinant of plant growth and differentiation. Directional auxin transport and auxin responses are required for proper embryogenesis, organ formation, vascular development, and tropisms. Members of several protein families, including the PIN auxin efflux facilitators, have been implicated in auxin transport; however, the regulation of auxin transport by signaling proteins remains largely unexplored. We have studied a family of four highly homologous AGC protein kinases, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
211
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(215 citation statements)
references
References 59 publications
4
211
0
Order By: Relevance
“…We found that PIN1 phosphorylation was not detectably impaired in complex mutants of the D6PK and PIDrelated kinases, suggesting that other protein kinases (e.g., other protein kinases of the AGCVIII family) also regulate PIN phosphorylation in addition to D6PKs and PID/WAGs. This hypothesis finds indirect support in the observation that root growth and gravitropism are not as severely impaired in the complex d6pk or pid/wag mutants as may be expected from mutants with severely impaired PIN and auxin transport function (10,17,20,31,35). Several of the phosphorylation events observed in our experiments support the notion that these, as yet, unknown PIN1-regulatory protein kinases are related-in their cell biological behavior-to D6PK and PID.…”
Section: Pin1 Phosphorylation Can Be Detected At the Basal Domains Insupporting
confidence: 61%
See 2 more Smart Citations
“…We found that PIN1 phosphorylation was not detectably impaired in complex mutants of the D6PK and PIDrelated kinases, suggesting that other protein kinases (e.g., other protein kinases of the AGCVIII family) also regulate PIN phosphorylation in addition to D6PKs and PID/WAGs. This hypothesis finds indirect support in the observation that root growth and gravitropism are not as severely impaired in the complex d6pk or pid/wag mutants as may be expected from mutants with severely impaired PIN and auxin transport function (10,17,20,31,35). Several of the phosphorylation events observed in our experiments support the notion that these, as yet, unknown PIN1-regulatory protein kinases are related-in their cell biological behavior-to D6PK and PID.…”
Section: Pin1 Phosphorylation Can Be Detected At the Basal Domains Insupporting
confidence: 61%
“…as with decreases in directional auxin transport in stems and hypocotyls (13,16,17). Thus, PIN1 phosphorylation is essential for auxin transport in planta and may allow predicting PIN1 activity in situ.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…The polar PIN localization determines direction of the auxin flow; thus, any signal that acts upstream to control the cellular PIN localization and activity can be translated into changes in the auxin distribution that modulate multiple aspects of the plant development. Phosphorylation has been shown to be important for auxin transport and distribution (17)(18)(19)(20). So far, the only known regulators that specifically regulate the PIN polar targeting are the serine/threonine protein kinase PINOID (PID) (18-20) and the protein phosphatase 2A (PP2A) (21, 22) that mediate antagonistically the phosphorylation of PIN proteins (22).…”
mentioning
confidence: 99%
“…Interestingly, although loss of phototropin 1 (the blue light receptor belonging to the AGC2 subgroup) impaired PIN3 polarization in the hypocotyl endodermis, it did not directly phosphorylate the PIN3 hydrophilic loop in vitro (Ding et al, 2011). Zourelidou et al (2009) reported that D6PK (D6 protein kinase), another AGC1 subgroup protein kinase, might be implicated in auxin transport, most likely by modulating PIN activity. D6PK was able to phosphorylate the hydrophilic loop of several PINs in vitro and in Arabidopsis protoplasts.…”
Section: Agc1 Kinases Directly Phosphorylate the Pin Hydrophilic Loopmentioning
confidence: 99%